The Model of Early Childhood Development Promotion with Family and Community Participations - Soiphet, Nutcha; Noimorkunladech, Napattamon; Pongnimitporn, Sarun; Chaimakham, Kamontip (Journal of The Royal Thai Army Nurses, 2023)
This action research aimed to develop a model for promoting early childhood development through family and community participations. The sample group consisted of 10 community leaders and 34 early childhood primary caregivers. The data were collected by using creative brainstorming techniques from family and community participations. The research tools included 1) the observation record form, 2) questions with the content validity index of 0.85 in the brainstorming creativity, 3) Early Childhood Development Surveillance and Promotion Manual (DSPM), 4) the model of early childhood development promotion with family and community participations with content validity index of 0.96, 5) the knowledge questionnaire on early childhood development promotion and vaccination with content validity index of 0.95; the reliability value of 0.82, and 6) the behavior questionnaire with content validity index of 0.92; reliability value of 0.84. The statistical analyses used to analyze the data were percentage, mean, standard deviation, and comparison of the results of the sample group by using the paired samples t-test. It was found that the model for promoting early childhood development through family and community participations consisted of knowledge sets to promote early childhood development suitable for their ages and vaccine literacy. The mean scores of knowledge and child development promotion behaviors and vaccines before and after using the model were significantly different at the level of .05.